Nutrient resorption in wetland macrophytes: comparison across several regions of different nutrient status - Rejmankova, E (The New phytologist, 2005)
• This study explored patterns of nutrient resorption in wetland macrophytes to test the prediction that plants from regions with a strong nutrient limitation will show higher resorption of the limiting nutrient. • Nitrogen and phosphorus resorption was assessed in macrophytes from marshes of different nutrient status in tropical and temperate regions, and expressed as resorption efficiency (NRE, PRE) and proficiency (NRP, PRP). Macrophytes were grouped into three categories: Typha, graminoids and broadleaved plants. • Nitrogen was less limiting than P, consequently N availability varied less than P availability, NRP and NRE were lower, and N resorption was mostly incomplete. NRP was determined more by growth form than by local conditions. The large range of soil P concentrations allowed an exploration of relationships between P availability and resorption along a wide gradient. P-limited macrophytes (N : P > 16) had significantly higher PRP and PRE. Resorption proficiency was found to be a more sensitive indicator of changes in nutrient availability than resorption efficiency. • The results confirmed that resorption in wetland macrophytes depends on nutrient availability, and is higher at nutrient-limited sites. A particularly strong relationship was found between resorption indicators and P limitation expressed either as live tissue N : P or soil P.